Facile construction of non-precious iron nitride-doped carbon nanofibers as cathode electrocatalysts for proton exchange membrane fuel cells - Palaniselvam, Thangavelu; Kannan, Ramaiyan; Kurungot, Sreekumar (Chemical Communications, 2011)
We demonstrate a facile construction of iron nitride-doped carbon nanofiber by effectively utilizing the existing slit pores and rough edges along the inner wall of the substrate as originated by virtue of its cup-stack structure for effectively increasing the number of active sites and consequently the oxygen reduction activity.